Developments since the Fourth WTO Minsterial Conference : technical assistance and capacity-building (International Centre for Trade and Sustainable Development GenevaCH, 2003)
Provides a background to the topic and lists the mandated deadlines. Focuses on the current state of play, highlighting the technical assistance plan for 2003; the situation with least-developed countries; and, the integrated framework
Keywords: TRADE NEGOTIATIONS